THE RELATIONSHIP BETWEEN INTEREST LEARNING, DISCIPLINE LEARNING, AND PARENT'S ATTENTION WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII - Putri Utami Wijayanti; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2019)
Some factors influence math learning results. The interest of learning, the discipline of learning, and parent attention hypothetically are the factors which are influenced the math learning result. The objective of this research is to find whether there are positive and significant relations between the interest of learning, the discipline of learning and the parent attention, and the math learning result of the student in grade VIII on Junior High School (SMP) Muhammadiyah Ponjong Gunungkidul Regency in the academic year of 2016/2017. This research population was the students of VIII grade in SMP Muhammadiyah Ponjong Kabupaten Gunungkidul Semester Genap Tahun Ajaran 2016/ 2017, consisting of class VIIIA, VIIIB, VIIIC totaling 63 students. Samples were taken from VIIIB as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect interest learning, discipline learning, and parents' attention and test method to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between interest learning, discipline learning, and parent's attention class VIII in even Semester of SMP Muhammadiyah Ponjong Gunungkidul Regency in the academic year of 2016/2017. It is showed by Fcount Â Ftable is 4,7048 > 3,1599 with R = 0,6629 and R2 = 0,4395 with ,with RC = , RC = Â and RC = 31,572 , EC = , SE = Â and EC = .